ChemInform Abstract: Sorption of Radionuclides from Aqueous Systems onto Graphene Oxide‐Based Materials: A Review. Issue 32 (August 2015) - Yu, Shujun; Wang, Xiangxue; Tan, Xiaoli; Wang, Xiangke
Abstract Review: 212 refs.